STRENGTHENING UNDERSTANDING OF THE IMPORTANCE OFDIGITAL INVESTMENT AMONG UIN GUSDURPEKALONGAN STUDENTS: PENGUATAN PEMAHAMAN PENTINGNYA INVESTASI DIGITAL DIKALANGAN MAHASISWA UIN GUSDUR PEKALONGAN - Arditya Prayogi; Imam Prayogo Pujiono; Dimas Setiaji Prabowo; Rohmad Abidin (PT. ROCE WISDOM ACEH, 2024)
An understanding of digital investment, especially in the current era ofdisruption, is urgently needed by all groups, including students who arefamiliar with the development of digital technology. Digital investment needsto be promoted from an early age by utilizing the current technologicalopportunities. Thus, this community service activity was carried out with theaim of strengthening participants' understanding of digital investment andpracticing it in the form of creating accounts and content on Blogs andYoutube. With this digital investment, it is hoped that students will have a goodunderstanding and can benefit from this investment in the future. This serviceactivity was carried out using the service learning method by giving theoreticallectures and direct practice. From the results of the activity, it was found thatthe activity participants had a good understanding of the material presented andhad basic skills related to digital investment by having Blog and Yotubeaccounts and being able to produce content as part of digital investment. Thisactivity also has a social impact based on the good response given by theparticipants during the activity.